Is ‘Green’ Gold and Silver Nanoparticle Synthesis Environmentally Friendly? - Lucas Reijnders (Nanomaterials)
In scientific literature biosynthesis of gold and silver nanoparticles and synthesis of these nanoparticles using small organic molecules such as citrate have been called: ‘green’. It has also been often stated that ‘green’ synthesis of gold and silver nanoparticle is environment(ally) friendly or ecofriendly. The characterization environment(ally) friendly or ecofriendly is commonly comparative. The comparison is between ‘green’ and ‘chemical’ synthesis. The few available comparative life cycle assessments addressing the environmental impacts of ‘green synthesis’ of Ag and Au nanoparticles, if compared with ’chemical’ synthesis, strongly suggest that a ‘green’ synthesis should not be equated with being environment(ally) friendly or ecofriendly. The term ‘green’ for Au and Ag nanoparticles obtained by ‘green’ synthesis is a misnomer. There is a case for only using the terms ecofriendly or environment(ally) friendly for nanoparticle synthesis when there is a firm basis for such characterization in comprehensive comparative cradle-to-nanoparticle life cycle assessment, taking into account the uncertainties of outcomes.